STUDI EFEKTIVITAS STRATEGI PEMASARAN HIJAU DALAM MENARIK KONSUMEN PADA PRODUK RAMAH LINGKUNGAN - Mulyadi, Tirta; Nurhayati, Siti; Lestari, Utami Puji; Asir, Muhammad; Launtu, Ansir (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to explore the effectiveness of green marketing strategies in attracting consumers to eco-friendly products. Amid growing environmental awareness, consumers are increasingly choosing products with minimal environmental impact. Green marketing strategies involve incorporating eco-friendly elements into products and marketing processes designed to enhance the sustainability values and corporate social responsibility. This article utilizes a literature review method to analyze various green marketing strategies, such as using recycled materials, eco-friendly packaging, and communication emphasizing ecological benefits. Based on the literature review findings, green marketing has proven effective in increasing consumer interest and fostering brand loyalty. However, challenges in implementation, such as consumer perceptions of the honesty and credibility of green claims, still exist. This study provides insights on how companies can optimize green marketing strategies to expand their consumer base while maintaining their commitment to environmental sustainability